2021
DOI: 10.1111/cdev.13638
|View full text |Cite
|
Sign up to set email alerts
|

Racial discrimination and the moderating effects of racial and ethnic socialization on the mental health of Asian American youth

Abstract: Asian Americans face structural racism and experience racial discrimination (see Benner et al., 2018, for review). In the last few years, anti-immigrant and racist sentiments have increased dramatically. Although anti-Asian crimes are rarely reported, Asian Americans, more than 62% of whom are foreign-born (U.S. Census Bureau, 2018), have been disproportionately targeted during this period. Nationwide, racist and antiimmigrant hate crimes targeting Asian Americans grew by 30% between 2015 and 2018-increasing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 51 publications
0
12
1
Order By: Relevance
“…Our overall discrimination prevalence rates are similar to other study findings, but we found no differences across East Asian and other Asian subgroupings, which is not consistent with past research (Hahm et al, 2021; Park et al, 2021). These similar rates of discrimination may reflect the perception of Asian Americans being a monolithic, homogeneous group and the racialization of disease.…”
Section: Discussioncontrasting
confidence: 56%
“…Our overall discrimination prevalence rates are similar to other study findings, but we found no differences across East Asian and other Asian subgroupings, which is not consistent with past research (Hahm et al, 2021; Park et al, 2021). These similar rates of discrimination may reflect the perception of Asian Americans being a monolithic, homogeneous group and the racialization of disease.…”
Section: Discussioncontrasting
confidence: 56%
“…The Orientalist climate exacerbated by the COVID-19 pandemic has led to increased public attention toward anti-Asian racism. Prior to the pandemic, Asian American adolescents and young adults experienced varied levels and frequencies of racist harassment (37,38) and depressive symptoms (15). Given the U.S.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are problematic as higher levels of racial discrimination are associated with more psychological distress and poorer mental health among parents and youth (Cheah et al, 2020; V. W. Huynh et al, 2022; Oh et al, 2022; Park et al, 2021; Zong et al, 2022). However, the quantitative data do not tell us how parents experienced and interpreted their racist incidents, how they discussed racism with their adolescents at home, and what they would prefer schools to do to support Asian American students in the event of COVID-19-related racism.…”
Section: Historical Background and Asian American Stereotypesmentioning
confidence: 99%